The inspiration and truth of scripture : testing the Ratzinger paradigm - Pidel, Aaron (Verbum Domini (Series), 2023)
"What does it mean to say that Scripture is God's Word? And just how true is the Bible? Though sometimes dismissed as "fundamentalist" concerns, these questions also sent twentieth-century Catholic theology searching for a new paradigm of biblical inspiration. Theologians repeatedly attempted to reconcile the traditional conviction that the Bible shares in the omniscience of its divine author with scholarly findings that suggested otherwise. Joseph Ratzinger contributed both negatively and positively to this project, deconstructing the regnant manualist models of inspiration and constructing an alternative inspired by St. Bonaventure. The result is an ecclesial model of surprising comprehensiveness and balance. Indeed, The Inspiration and Truth of Scripture concludes that Ratzinger's alternative provides the least inadequate paradigm currently on offer. The Inspiration and Truth of Scripture breaks new ground in several ways. First, it situates Ratzinger within a broader Catholic quest for a theology of inspiration, showing his model offers advantages even relative to those proposed by modern theology's most eminent minds: John Henry Newman, Pierre Benoit, Karl Rahner, and David Tracy. Secondly, this book shows how Ratzinger's paradigm generates "tests" for identifying the perennially valid affirmations of Scripture, and thus an approach to resolving disputed biblical questions. Must one who accepts the authority of Scripture believe in the Devil? Are the Marian dogmas really "in" Scripture? To what extent does Jesus's prohibition of divorce still apply in today's changed social circumstances? Just how historical are Gospel narratives, like the Last Supper, intended to be? The result is a book that bridges the gap between normative theology and historical exegesis. Overall, The Inspiration and Truth of Scripture presents Ratzinger not as an unimaginative enforcer of doctrinal conclusions but as a creatively faithful theologian, whose reconfiguration of inspiration should serve as the point of departure for all future reflection on the subject"--